Numerus as the Metaphysical Principle in St. Augustine’s Doctrine of Rhythm - Tashchian, Andrey (Laval théologique et philosophique, 2014)
In St. Augustine’s doctrine of rhythm numerus manifests the metaphysical ascent from sensuousness to rationality and is the ontological root of finite beauty. Moreover, numerus is differentiated into the objective and subjective spheres, proving to be a totality, the “idea.” Meanwhile, as a formation of antique culture, this concept is not known as a real contradiction, and thereby eternal numeri are not posited as a process in which finite subjectivity, I would be a necessity for the infinite substance. So, in St. Augustine’s doctrine the essence of the science of music has not the value of man’s self-conscious activity.